If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -15 = x + 36 Reorder the terms: -15 + 3x = x + 36 Reorder the terms: -15 + 3x = 36 + x Solving -15 + 3x = 36 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -15 + 3x + -1x = 36 + x + -1x Combine like terms: 3x + -1x = 2x -15 + 2x = 36 + x + -1x Combine like terms: x + -1x = 0 -15 + 2x = 36 + 0 -15 + 2x = 36 Add '15' to each side of the equation. -15 + 15 + 2x = 36 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = 36 + 15 2x = 36 + 15 Combine like terms: 36 + 15 = 51 2x = 51 Divide each side by '2'. x = 25.5 Simplifying x = 25.5
| y=(2+4)(3-4) | | 1.4x=0.1x+52 | | x=600-2x^2 | | 4x+2(x+1)=14 | | -4x-(5)=30 | | y=4(.75)-12 | | 3w-2x-y+6w+15x-6y= | | .24=-18z | | 5x-3y+15w-4y-6w+8x= | | y=2lnx-8x | | 6w+8y+5x+8x-15y+3w= | | 4y-12=2y+40 | | -3(4)+y=-5 | | 2x+10=10x-48 | | 85-3x=8+19 | | 0=8-24x-12x^2 | | 10x+18y=12 | | 5(8-3x)=55 | | 3(2x+7)-4=7-5(4-3x) | | x^2+32x+128=0 | | X^2-2(x-2)020=20 | | 2x+11=-33-x | | [n-1]*4=28 | | x^2+-2x+2=0 | | 4n+2n=21+7 | | 8a+1=25 | | x^2-12x+8y+20=0 | | ln(y)=x-ln(C) | | 12x-220=2x-10 | | 89-6x=21x+17 | | 5+x=-20 | | -2x-(-8)=-8 |